2022
DOI: 10.1073/pnas.2120432119
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni spreading and contracting three-component droplets on completely wetting surfaces

Abstract: Significance The shape and dynamics of small sessile droplets are dictated by capillary forces. For liquid mixtures, evaporation adds spatio-temporal modulation to these forces that can either enhance or inhibit droplet spreading, depending on the direction of the resulting Marangoni flow. This work experimentally and numerically demonstrates the coexistence of two antagonistic Marangoni flows in a ternary mixture. Played against each other, they can choreograph a boomerang-like wetting motion: Dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In figure 7, the fluid dynamics is neglected. By considering the complex fluid dynamics of multicomponent evaporation, some other phenomena can be observed, such as Ouzo effect (Diddens et al 2017;Lohse & Zhang 2020), pancake structure (Pahlavan et al 2021), precursor film , interfacial instability (Keiser et al 2017;Baumgartner et al 2022) and Taylor dispersion (Charlier et al 2022).…”
Section: Evaporationmentioning
confidence: 99%
“…In figure 7, the fluid dynamics is neglected. By considering the complex fluid dynamics of multicomponent evaporation, some other phenomena can be observed, such as Ouzo effect (Diddens et al 2017;Lohse & Zhang 2020), pancake structure (Pahlavan et al 2021), precursor film , interfacial instability (Keiser et al 2017;Baumgartner et al 2022) and Taylor dispersion (Charlier et al 2022).…”
Section: Evaporationmentioning
confidence: 99%
“…Nonetheless, models based on the lubrication approximation will be required when the mixtures components have similar vapor pressures to predict the temporal changes in mixture composition. 18,29,30,68 ■ CONCLUSIONS This study investigates the evaporation of droplets containing octamethyltrisiloxane and ethanol on a wettable surface. The findings indicate that the droplets exhibited four distinct wetting dynamics: two contracting and two spreading.…”
Section: ■ Evaporation Rate and Drying Periodsmentioning
confidence: 99%
“…11−14 These factors influence the wetting dynamics and contact angle during evaporation. 15−17 Baumgartner et al 18 demonstrated that droplets containing a fully miscible ternary mixture (water, ethanol, and propylene glycol), deposited on completely wetting surfaces, exhibit rich wetting dynamics as selective evaporation and surface tension gradients can change the droplet shape and result in three different wetting behaviors. Furthermore, the aforementioned factors in multi-component droplet evaporation also play a crucial role in understanding deposit patterns when polymers or particles are included.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, evaporation in multicomponent liquids can trigger phenomenologically richer secondary processes compared to pure liquids. Such secondary processes include fluid flows [44,46,52], nontrivial contact line motion [53], segregation [49,54], and phase separation [48] (Figure 1.5). We discuss a few of these processes below: (a) Solutal Marangoni flow by selective evaporation Selective evaporation of the more volatile liquid in droplets and capillaries results in spatial gradients in concentration.…”
mentioning
confidence: 99%